Optimum Design of Laminated Corrugated Metal Gasket Using Computer Simulation - Haruyama, Shigeyuki; Choiron, Moch. Agus; Nurhadiyanto, Didik (International Journal of Integrated Engineering, 2019)
Previous studies on corrugated metal gaskets using single material SUS 304 was clarified. However, the corrugated metal gasket for elastic model in contact with flange having high surface roughness was still leaking due to only partial contact occurs. Besides that, for gasket contact with another surface roughness of flange still need high axial force. Further development is needed to improve gasket perform. The basic problem of single material SUS 304 is lower of contact width. The contact stress is larger enough to reduce the internal pressure effect of piping. To increase the contact width between flange and gasket, it needed surface layer in the both outside of gasket. The layer materials should softer than base material. The layer material will stick on the outer surface of flange. The optimization analysis using simulation analysis. Simulation analysis using finite element method based on contact width and contact stress. The Taguchi method used to determine the optimum design. The optimum design of laminated corrugated metal gasket has been obtained. The dimension of laminated corrugated metal gasket is pitch 1 is 4.5mm, pitch 2 is 3.4 mm, pitch 3 is 4 mm, thickness of based material is 1,5 mm, radius is 1,5 mm, height is 0.35 and thickness of surface material is 0.1 mm. This gasket is better than corrugated metal gasket without laminated.